Mapping and Correlation Analysis of Efficiency and Profitability: The Case of Islamic Rural Bank in Indonesia - Titi Dewi Warninda; M. Nadratuzzaman Hosen (Al-Iqtishad: Jurnal Ilmu Ekonomi Syariah, 2015)
This research aims to analyze efficiency  and  profitability  of  Islamic  Rural  Banks  in  Indonesia  using Variable Returns to Scale model of Data Envelopment Analysis and efficiency-profitability matrix.  The  results  of  this  research  show  that  most  of  Islamic  Rural  Banks  are included in the Dog quadrant (high efficiency but low profitability) and Sleeper quadrant (low efficiency but high profitability). Meanwhile, the result of correlation analysis between efficiency and profitability indicates that efficiency has a negative correlation with profitability. Negative correlation of efficiency and profitability is in accordance with the result of efficiency-profitability matrix. The results of this research show that not all of Islamic Rural Bank which have high efficiency are also having high profitability.DOI:10.15408/aiq.v7i1.1354